KOMUNITAS WIBU SITUBONDO SEKAI: Sebuah Identitas Kebudayaan Yang Terbentuk Dalam Masyarakat Modern - Ahmad, Thifli; Jamil, Alfan; Zidan, Ahmad; Huda, Yusril (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Situbondo Sekai Community gathers individuals who have a sense of interest in Japanese culture and anime, or wibu for short. Interests and hobbies are one of the main reasons this community was formed. A very foreign culture is increasingly turning into a reality that eventually blends into society. Similarly, the Situbondo Sekai community takes cultural values from Japan, which they then use as the main foundation in building solidarity. Basically, a wibu's identity is based on his or her actions that are directly accepted by the outside community and subjective assessments from other individuals. So that in the end it will form a new knowledge that has been objectivized and agreed upon. Wibu are just like any other human being, what makes their label different from others is the community they choose. The community can represent their role in the context of interactions between fellow individuals.